Peran Pembelajaran Pemodelan Matematika di Sekolah - Ida Fitriana Ambarsari; Nur Hasanah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Some problems in real life can be solved by using mathematics. The first step to solving the problem is to formulate or represent the problem in mathematical language. The process of formulating or representing into mathematical language is referred to as mathematical modeling. The implementation of mathematical modeling in the classroom is still relatively new and rarely applied in the classroom. However, based on the statements of several experts, it is explained that mathematical modeling can be taught, studied and suggested to be implemented in the classroom. The purpose of this research is to present the results of studies from several sources data related to the implementation and the role or importance of implementing mathematical modeling learning in the classroom. The research method used in this research was literature review. Furthermore, based on the study of several literatures, it is found that learning mathematical modeling is recommended to be implemented in the classroom because it has many positive effects on students. Some researchers explain that learning mathematical modeling is important to be implemented in the classroom because it can improve students motivation, creativity, and independence in learning mathematics. However, it also explains some of the weakness of learning mathematical modeling and recommendations for follow-up.